An Evaluation of the Phenotypic Antibiotic Susceptibility of Potential Lactic Acid Bacteria Starter Cultures Isolated From Cambodian Fermented Foods - Ly, Dalin; Mayrhofer, Sigrid; Domig, Konrad J. (Frontiers in Food Science and Technology, 2022)
The development of indigenous starter cultures for producing fermented foods that meet the expectations of Cambodians is necessary to preserve the country’s food supply. In this study, the safety of 46 lactic acid bacteria strains based on the phenotypic antibiotic susceptibility to clinically relevant antibiotics was assessed. The antibiotic susceptibility of 39 lactobacilli and seven pediococci isolated from Cambodian fermented foods to 16 antibiotics was studied according to ISO 10932/IDF 233. The results were interpreted based on the minimal inhibition concentrations obtained, using differently defined breakpoints and concentration distributions as well as data from the scientific literature. Applying only breakpoints, the results demonstrated two Lactiplantibacillus pentosus, three Companilactobacillus futsaii, three Levilactobacillus namurensis and seven Pediococcus pentosaceus strains with acquired resistance. However, considering further information, one Companilactobacillus futsaii, one Limosilactobacillus fermentum and respectively three Lactiplantibacillus pentosus and Levilactobacillus namurensis strains would possess an acquired resistance. The genetic background for the absence of transmissible antibiotic resistances in lactic acid bacteria strains intended for food application must be confirmed by molecular methods for potential starter cultures.